Isolation and Idintification of candida albicans from vagina and Study of some Virulance Factors (Baghdad Science Journal, 2025)
197 vaginal swabs were collected from women of different ages. (60) Isolates of Candida albicans (30.4%) were obtained, and the other species of Candida represent (18.27%). Bacterial infections showed (41.11%), and infection with Trichomonas vaginalis was (2.03%). Ten isolates of C. albicans were chosen randomly for farther study which include two virulence factors tendency of adhesion wich showed a percentage of (52%) to(32%) , and the ability to produce phospholipaze enzyme and it’s activity which showed (50%) of the isolates have the ability to produce the enzyme in different degrees .